Evaluación de la incorporación de material reciclado EKO PE, mediante la realización de pruebas experimentales al proceso de inyección de huacales en la empresa Iberplast S.A.S (2021)
Currently the cesspool of the Iberplast SAS company are made from post-industrial and post-consumer box grinding with a dosage of 50% HDPE and virgin raw material with 50% HDPE, however, these raw materials have harmful effects on the environment. environment and human health. For this, a bibliographic search was carried out to identify the physicochemical and mechanical properties of the EKO PE material, then the injection process was carried out with u at 10% and 15% with the EKO PE material and finally an estimate of production costs was carried out. of the huacal for the container of non-carbonated beverages.